Sensory image according to Ibn al-Wardi (The visual image is a model) (Journal of Hama University, 2025)
The research represents a serious attempt to study the visual sensory image according to Ibn al-Wardi. The research focused solely on the visual image due to its importance. Sight is at the forefront of the senses that visualize everything that is happening around us, and the researcher considered it necessary to divide the visual image into four sections according to the method of presentation in which the poet presented his images, which are: the natural visual image, the realistic visual image, the optical visual image, and the color visual image; To facilitate their refutation and study, whether these sensory images are inspired by reality, or are based on retrieving images from the world of imagination by employing nature in formulating its images metaphorically, by relying on the actions of vision, its visual indicators, and its tools, taking advantage of the mechanisms used in dealing with the image, And focus on the visual aspects of its presentation.